Social media, politics and the state : protests, revolutions, riots, crime and policing in the age of Facebook, Twitter and YouTube - Trottier, Daniel; Fuchs, Christian, 1976- (New York : Routledge, 2015)
'This book is the essential guide for understanding how state power and politics are contested and exercised on social media. It brings together contributions by social media scholars who explore the connection of social media with revolutions, uprising, protests, power and counter-power, hacktivism, the state, policing and surveillance. It shows how collective action and state power are related and conflict as two dialectical sides of social media power, and how power and counter-power are distributed in this dialectic. Theoretically focused and empirically rigorous research considers the two-sided contradictory nature of power in relation to social media and politics. Chapters cover social media in the context of phenomena such as contemporary revolutions in Egypt and other countries, populism 2.0, anti-austerity protests, the fascist movement in Greece's crisis, Anonymous and police surveillance'--
Theorising social media, politics and the state: an introduction / Daniel Trottier and Christian Fuchs -- Social networking sites in pro-democracy and anti-austerity protests: some thoughts from a social movement perspective / Donatella Della Porta and Alice Mattoni -- Populism 2.0: social media activism, the generic internet user and interactive direct democracy / Paolo Gerbaudo -- Anonymous: hacktivism and contemporary politics / Christian Fuchs -- The rise of Nazism and the web: social media as platforms of racist discourses in the context of the Greek economic crisis / Panos Kompatsiaris and Yiannis Mylonas -- More than an electronic soapbox: activist web presence as a collective action frame, newspaper source and police surveillance tool during the London G20 protests in 2009 / Jonathan Cable -- Assemblages: live streaming dissent in the'Quebec spring' / Elise Danielle Thorburn -- Creating spaces for dissent: the role of social media in the 2011 Egyptian revolution / Sara Salem -- Social media activism and state censorship / Thomas Poell -- Vigilantism and power users: police and user-led investigations on social media / Daniel Trottier -- Police'image work' in an era of social media: YouTube and the 2007 Montebello summit protest / Christopher J. Schneider.
Includes bibliographical references and index.
Keywords: Internet -- Political aspects; Political participation; Social media -- Political aspects; Political psychology